Cirurgia fetal em Brasília - Costa Rezende, Juliana (2018)
Brasilia is the capital of Brazil. There are currently two public hospitals in the city that are able to perform fetal surgery: Hospital Materno-Infantil de Brasília (HMIB) and Hospital Universitário de Brasília (HUB). In this paper, we present the data from HUB. Ten patients underwent invasive procedures during pregnancy in the last five years. There was one intrauterine transfusion (cordocentesis) and zero laser ablation for monochorionic diamniotic pregnancy or fetal endotracheal occlusion for diaphragmatic hernia. The paucity of cases is mainly due to a failure in the diagnosis and a delay in the reference to tertiary centers.